Reaping the Benefits from Global Value Chains - Cheng, Kevin; Rehman, Sidra; Seneviratne, Dulani; Zhang, Shiny (Washington, D.C. : International Monetary Fund, 2015)
Against the backdrop of the rise of global value chains (GVCs), particularly in Asia, this paper documents key developments of GVCs and investigates what factors cause economies to reap greater benefits from GVC participation. Key findings include: first, moving toward a more upstream position in production and raising economic complexity are associated with the country increasing its share of GVC value added. Second, fostering GVC participation and expanding the share of the domestic value added in a value chain require efforts to reduce trade barriers, enhance infrastructure, foster human capital formation, support research and development, and improve institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet